Isolation, purification, and structural elucidation of Stropharia rugosoannulata polysaccharides with hypolipidemic effect - Gao, Yinlu; Abuduaini, Gulijiannaiti; Yang, Chenhe; Zhang, Shanshan; Zhang, Yanrong; Fan, Hongxiu; Teng, Xu; Bao, Chenligen; Liu, Hongcheng; Wang, Dawei; Liu, Tingting (Frontiers in Nutrition, 2022)
Stropharia rugosoannulata polysaccharides, named SRF-3, was derived from the S. rugosoannulata by freezing and thawing combine water extraction, DEAE-cellulose column and Sephacryl S-200 HR gel preparation column, and its hypolipidemic activity was determined. The structural characteristics of SRF-3 were analyzed by infrared spectral scanning, ultra-high performance liquid chromatography (UHPLC), acid hydrolysis, methylation analysis, nuclear magnetic resonance (NMR), and GC-MS. SRF-3 is composed of mannose, galactose, methyl galactose and fructose with ratios of 16, 12, 58 and 12, respectively. In addition, the average relative molecular mass of SRF-3 is approximately 24 kDa. The main chain of SRF-3 is mainly composed of repeating α-D-1,6-Galp and α-D-1,6-Me-Galp units, with branches in the O-2 position of Gal. The structure is presumed to be a mannogalactan, with a small amount of t-β-D-Manp present as a side chain. Hypolipidemic activity assay showed that SRF-3 had good antioxidant and hypolipidemic effects in vitro, suggesting that SRF-3 may have potential application in reducing liver fat accumulation.